NASA robotics research for planetary surface exploration. - Weisbin, C.R (IEEE Robotics and automation magazine)
The surface systems technology under development has long-range objectives that are quite challenging and will lead to revolutionary capabilities. Many of the technologies needing development are in their infancy: multiple, coordinated multiscale (small and large) special robots forming networks; Remote robotic work systems; Extension of lifetime and power performance envelopes by orders of magnitude; Local robotic outpost communication architectures and systems, high-rate surface switching and aggregation centers, and/or aero-synchronous network relays; Manufacture of propellants, oxygen, water, and other resources. However, substantial initial steps are being made toward the long-range goals by seeking and supporting activities that lead to early proof-of-principle experiments in selected areas. Evolution of the technology and infusion into flight systems will require major achievements from the community of researchers involved, and this effort will be interesting and exciting